Electromyographic analyses of the erector spinae muscles during golf swings using four different clubs - Sorbie, G. G.; Grace, F. M.; Gu, Y.; Baker, J. S.; Ugbolue, U. C. (Journal of Sports Sciences, 2017)
The purpose of this study was to compare the electromyography (EMG) patterns of the thoracic and lumbar regions of the erector spinae (ES) muscle during the golf swing whilst using four different golf clubs. Fifteen right-handed male golfers performed a total of twenty swings in random order using the driver, 4-iron, 7-iron and pitching-wedge. Surface EMG was recorded from the lead and trail sides of the thoracic and lumbar regions of the ES muscle (T8, L1 and L5 lateral to the spinous-process). Three-dimensional high-speed video analysis was used to identify the backswing, forward swing, acceleration, early and late follow-through phases of the golf swing. No significant differences in muscle-activation levels from the lead and trail sides of the thoracic and lumbar regions of the ES muscle were displayed between the driver, 4-iron, 7-iron and pitching-wedge (P > 0.05). The highest mean thoracic and lumbar ES muscle-activation levels were displayed in the forward swing (67-99% MVC) and acceleration (83-106% MVC) phases of the swing for all clubs tested. The findings from this study show that there were no significant statistical differences between the driver, 4-iron, 7-iron and pitching-wedge when examining muscle activity from the thoracic and lumbar regions of the ES muscle.